PELATIHAN BAHASA INGGRIS BAGI WARGA DESA MENDEN UNTUK MENGHADAPI ERA GLOBALISASI - Setyowati, Erna; Widayanti, Sukasih Ratna; Haryanti, Sri; Setiawati, Endang Eko Djati; Setyandari, Ana; Sholihah, Umi; Anisa, Ike (LPPM Universitas Widya Dharma Klaten, 2023)
The use of English is very important nowadays. As the English teachers, we have a duty to share our knowledge to the society. English training is one activity that can be applied. In Menden Village, Kebonarum District, Klaten Regency, we were held this English training to the people who live there to become the participants. This activity is aimed to foster participants’ interest in mastering English, to provide additional basic knowledge of English, and to provide a way of learning English with specific strategies. It is hoped that this activity can be useful to their daily life to face the globalization era.